Enhancement of higher order thinking skills through empowerment of learning environments - Jamaluddin, Nor Sa'adah; Abdul Kadir, Suhaida; Abdullah, Arnida; Alias, Siti Noormi (Human Resource Management Academic Research Society, 2019)
Higher Order Thinking Skill (HOTS) is an important skill that is focused in the six aspirations for students through Education Development Plan of Malaysia (EDPM) 2013-2025. Preparing students who are able to master HOTS remain the global education challenge due to the importance of this skill in students in order to prepare them with high marketability value in the future. The transformation of students’ low order thinking skill towards high order thinking skill will be able to produce students who are rooted nationally but think internationally which will altogether create Malaysia’s education system that is equivalent of international education system. Students’ mind transformation can be developed through involvement of learning environment elements which are closely related to the application of HOTS in schools. Thus, this concept paper was written to put forward the issues related to learning environment elements that includes teaching and classroom environment in the application of HOTS among students. The discussions in this article takes into consideration the issues focused by Education Development Plan of Malaysia (EDPM) 2013-2025 that emphasizes HOTS among students in order to create marketability and thus contribute towards the success of nation’s education and economic aspects. This research also suggested a few points of improvements related to the discussed issues, as well as provide guideline to ensure HOTS can be successfully cultivated among students.